Improving outpatient services: the Southampton IBD virtual clinic. Issue 2 (13th March 2012) - Hunter, Jo; Claridge, Andrew; James, Shirley; Chan, David; Stacey, Bernard; Stroud, Mike; Patel, Praful; Fine, David; Cummings, J R Fraser
Abstract : The follow-up of inflammatory bowel disease (IBD) patients is challenging due to the relapsing remitting nature of the diseases, the wide spectrum of severity and complexity as well as the need for monitoring of long-term complications and drug treatments. Conventional outpatient follow-up lacks flexibility for patients and there are competing pressures for clinic time. Alternative follow-up pathways include telephone clinics, self-management programmes or discharging patients. The IBD virtual clinic (VC) is a further option. Patients with an established diagnosis for >2 years, who have been stable for >1 year, do not have primary sclerosing cholangitis and who give their consent, are entered into the VC system. Two months before their annual follow-up is due patients are sent blood test forms and a simple questionnaire with an information sheet. If they meet any of the criteria on the questionnaire, they are asked to contact the IBD specialist nursing team to discuss their situation. The blood test results and the patient's database entry are reviewed to ensure that they are not due surveillance investigations. The patients and their GPs then receive a letter informing them of their management plan. We currently follow-up 20% of the Southampton IBD cohort using the VC. The VC system is an innovative, efficient and patient-responsive method for following up mild to moderate IBD. It is well liked by patients but is dependent on a well-maintained database with good integration of IT systems and requires both clerical and IBD nurse specialist support.